Proposal for a philosophy of the Internet - Ropolyi, László (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The paper argues for the necessity of building up a philosophy of the Internet and proposes a version of it, an «Aristotelian» philosophy of the Internet. First, an overview of the recent trends in the Internet research is presented. This train of thoughts leads to a proposal of understanding the nature of the Internet in the spirit of the Aristotelian philosophy i. e., to conceive the Internet as the Internet, as a totality of its all aspects, as a whole entity. For this purpose, the Internet is explained in four (easily distinguishable, but obviously connected) contexts: we regard it as a system of technology, as an element of communication, as a cultural medium and as an independent organism. Based on these investigations we conclude that the Internet is the medium of a new mode of human existence created by late modern man; a mode that is built on earlier (i. e., natural, and social) spheres of existence and yet it is markedly different from them. We call this newly formed existence web-life. Finally using two enlightening cultural-historical analogies (the reformation of knowledge and the formation of web-life) several fundamental characteristics of the web-life is presented.